Re:GEN An Alternative to Occupying Urban Space - Crotty, Kelsey A (My University, 2020)
Cities are growing at unprecedented rates. Simultaneously, society is beginning to experience physicality through a combined digital and social frame. We currently live within an economic and real estate system whose rigidity makes generating equity, finding quality, affordable space, and fostering community simultaneously difficult. It is apparent that new forms of habitation, that draw on changing contemporary conditions, are becoming critical. Re:GEN is the speculative design of a new system that leverages changing economic and digital social structures as a means to employ a form of the sharing paradigm within the built environment. This thesis proposes that architecture, as both a profession and design, can leverage the resource-exchange platforms already available while advocating for a community-based culture, addressing many of the problems of high-density living in urban environments. Re:GEN, as the catalyst of a new collective development pattern, offers an alternative method to occupying space as an exploration into the future of high-density living.
Thesis (Master's)--University of Washington, 2020
Keywords: Architecture; Design; future living; social development; Spatial relationship; Urban Design; Architecture; Architecture